Incidence of maternal mortality mobi with hypertensive disorders in pregnancy: Provincial Hospital General Docente Riobamba - Hidalgo Cajo, Byron Geovanny; Nina Mayancela, Wilson Lizardo; Hidalgo Cajo, Diego Patricio; Mayacela Alulema, Angel Gualberto; Satan Gunza, Luis Gerardo; Hidalgo Cajo, Ivan Mesias (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2017)
Research identifies the incidence of maternal mortality mobi with hypertensive disorders in pregnancy. A retrospective, descriptive, correlational and cross-sectional study with a sample of 205 pregnant was performed. 94.6% had pre-eclampsia and eclampsia 4.8% triggered with; with respect to age comprise 76% between 18 and 34 years, 51.7% had complications before, during and after childbirth, 45% with HELLP syndrome, 9% retention of placental remains and postpartum hemorrhage and reached 3% maternal death. We conclude that a good primary health care will decrease the incidence of hypertensive disorders in pregnancy.